2020
DOI: 10.1017/jpa.2020.60
|View full text |Cite
|
Sign up to set email alerts
|

A new crocodylid from the middle Miocene of Kenya and the timing of crocodylian faunal change in the late Cenozoic of Africa

Abstract: Brochuchus is a small crocodylid originally based on specimens from the early Miocene of Rusinga Island, Lake Victoria, Kenya. Here, we report occurrences of Brochuchus from several early and middle Miocene sites. Some are from the Lake Victoria region, and others are in the Lake Turkana Basin. Specimens from the middle Miocene Maboko locality form the basis of a new species, Brochuchus parvidens, which has comparatively smaller maxillary alveoli. Because of the smaller alveoli, the teeth appear to be more wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 90 publications
(200 reference statements)
2
18
0
Order By: Relevance
“…They also assembled a second combined dataset that included 189 morphological characters for 15 extant and 85 extinct taxa from Brochu 46 and stratigraphic data. The larger dataset in their study includes several new characters as well as modifications to characters and codings used in previous analyses; our close examination of this dataset reveals incorporated errors 36 , 108 , and results should thus be treated with caution.…”
Section: Methodsmentioning
confidence: 99%
“…They also assembled a second combined dataset that included 189 morphological characters for 15 extant and 85 extinct taxa from Brochu 46 and stratigraphic data. The larger dataset in their study includes several new characters as well as modifications to characters and codings used in previous analyses; our close examination of this dataset reveals incorporated errors 36 , 108 , and results should thus be treated with caution.…”
Section: Methodsmentioning
confidence: 99%
“…Tooth crown morphologies are consistent with size and shape heterodonty in brevirostrine taxa (Figure 10B) (D’Amore, Harmon, Drumheller, & Testin, 2019; Kieser, Klapsidis, Law, & Marion, 1993). Although represented by small sample sizes, maximum tooth crown lengths indicate body sizes similar to comparatively small-bodied crocodylids from the Paleogene and early to middle Miocene of North African and sub-Saharan formations (Brochu & Gingerich, 2000; Conrad et al, 2013; Cossette et al, 2020), as opposed to the gigantic late Miocene-Pleistocene taxa from East Africa (Brochu & Storrs, 2012; Storrs, 2003). A single broken, poorly preserved tooth is elongate and slightly recurved distally, similar to the condition in longirostrine, piscivorous tomistomine and gavialoid taxa, suggesting the presence of at least two crocodylid taxa in the lower member of the Mazamba Formation.…”
Section: Methodsmentioning
confidence: 99%
“…Euthecodon (Buffetaut, 1979; Tchernov & Couvering, 1978) and gharials referred by Storrs (2003) to Eogavialis Buffetaut, 1982 (Figure 1h) have been reported from sites near Lake Victoria and Lake Turkana, but otherwise, the crocodylian faunas appear to have been very different from those at higher stratigraphic levels. The only crocodylian not sporting a tubelike snout thus far reported from this interval is the small osteolaemine Brochuchus Conrad et al, 2013 (Figure 1d), which is unrelated to any generalized crocodylid found later in the Neogene and may not have exceeded 2.5 m in total length (Conrad et al, 2013; Cossette et al, 2020; Tchernov & Couvering, 1978). Nothing ecologically equivalent to large Crocodylus has previously been reported.…”
Section: Introductionmentioning
confidence: 95%
“…These, in turn, are thought to have led to diminishing woodlands and expansion of C 4 plants (e.g., Feakins et al, 2013; Jacobs et al, 2010; Linder, 2017; Saarinen et al, 2020). This prompted Cossette et al (2020) to suggest that changes in crocodylian faunas might have reflected changes in vegetation; modern African dwarf crocodiles ( Osteolaemus Cope, 1861; Figure 1b) are generally limited to forested wetlands (Amoah et al, 2021; Eaton, 2010; Kofron, 1992; Leaché et al, 2006; Riley & Huchzermeyer, 1999; Smolensky, 2015; Waitkuwait, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation